Targeting dipeptidyl peptidase-8/9 to combat inflammation-induced osteoclastogenesis in RAW264.7 macrophages and analysis of anti-osteoclastogenesis potential of chrysin - Syed Sufian Ahmad; Faraha Ahmed; Sayeed Ahmad; Anuja Krishnan; Mohammad Ahmed Khan (Iranian Journal of Basic Medical Sciences)
Objective(s): Osteoclasts drive bone resorption under inflammation, with cytokines promoting osteoclastogenesis. The role of proline enzymes like dipeptidyl peptidase-8 and 9 (DPP-8/9) in this process remains unclear. This study aimed to explore the DPP-8/9 involvement in inflammation-driven osteoclastogenesis using the RAW264.7 macrophage model.Materials and Methods: Receptor activator of nuclear factor-κB ligand (RANKL) and lipopolysaccharide (LPS) induced osteoclastogenesis, raising interleukin-6 (IL-6), tumor necrosis factor (TNF-α), and IL-23 levels. Using RAW264.7 cells, DPP-8/9 protein and tartrate-resistant acid phosphatase (TRAPc) were assayed. Antibodies for cluster of differentiation (CD86 and CD206) were used to analyze macrophage polarization, while molecular docking was used to assess flavonoid binding to DPP-8/9. Western blot confirmed DPP-8/9 expression in treated macrophages.Results: Administering RANKL and LPS increased IL-6 and TNF-α levels, significantly promoting osteoclastogenesis in RAW264.7 macrophages. This treatment also elevated the levels of the inflammatory macrophage marker IL-23. Osteoclast formation was confirmed by measuring TRAPc levels in the culture. Analysis of the cell supernatant revealed elevated DPP-8/9 levels in the RANKL+LPS group. Inhibition of DPP-8/9 with 1G244 decreased inflammatory cytokines and TRAPc levels in the cell culture. Molecular docking analysis of various flavonoids identified chrysin as a potential molecule with sufficient binding energy against DPP-8/9, a finding confirmed by blotting assay.Conclusion: This study emphasizes the involvement of DPP-8/9 in inflammatory osteoclastogenesis in RAW264.7 macrophages. Inhibition of DPP-8/9 reduced osteoclastogenesis markers and inflammatory cytokines levels, indicating decreased osteoclast formation. Additionally, chrysin demonstrated potential as an anti-DPP-8/9 agent, highlighting its possible role in future therapeutic strategies targeting inflammation-induced osteoclastogenesis.